A giant femoral pseudo aneurysm secondary to arteriovenous fistula following stab injury (Bangladesh Medical Journal Khulna, 2016)
Pseudo aneurysm wall is not formed by vascular tissue but develops from organized thrombus, associated fibrosis and surrounding tissue. Post stab injury pseudo aneurysm associated with arteriovenous fistula of lower limb is exceptional. Here one such case is reported who was operated 4 months after the incidence of stab injury in his way back home at an incidence of robbery. The patient was very poor and did not have the ability to seek higher medical care. He was moving everywhere with a big pulsatile mass on supero medial part of his left thigh. Lastly surgical intervention was done and the patient got well.Bang Med J (Khulna) 2015; 48 : 34-36